Battling Maternal Mortality Through Access to Primary Care Physicians [26F]. (May 2020) - Yadav, Ghanshyam S.; Angraal, Suveen; Turrentine, Mark; Nagarkatti, Nupur
Abstract : INTRODUCTION: Chronic disease among reproductive aged women has been implicated as one of the reasons for the high maternal mortality rate in the United States. Primary care physicians (PCPs) play a vital role in maintaining life-long health and in management of chronic diseases. We evaluated the association between prevalence of PCPs and maternal mortality rates. METHODS: County-level data on number of PCP's and maternal mortality rates in 2014 was obtained from the American Medical Association and National Vital Statistics System, respectively. County level population metrics from the Census Bureau were used to estimate the number of PCPs per 100, 000 population. Linear regression model was used to assess association of PCP rate with county-level age-standardized maternal mortality rates. Furthermore, we compared counties with no PCPs, with an equivalent number of counties with highest rate of PCPs. Relative risk reduction for maternal mortality was calculated. RESULTS: Data were available for 3069 (97.6%) counties. National maternal mortality rate (per 100, 000 population) in 2014 was 0.35 (95% CI 0.33–0.37). At the county level, number of PCPs per 100, 000 was negatively associated with maternal mortality rate after adjusting for various socio-demographic factors ( P <.001). 149 counties in the United States had no PCPs. When compared with 149 counties with highest number of PCPs per 100, 000 population, the maternal mortality rate was significantly higher (0.36 versus 0.28, respectively P <.01). CONCLUSION: Higher maternal mortality rates are noted in counties with a lower prevalence of PCP's. Improving access to PCPs may reduce maternal mortality rates in the United States.